Adsorption site engineering: Cu–Ni(OH)2 sheets for efficient hydrogen evolution. Issue 32 (9th August 2021) - Zhong, Wenda; Yang, Chenfan; Wu, Jing; Xu, Wenli; Zhao, Rong; Xiang, Hui; Shen, Ke; Li, Xuanke
Abstract : The introduction of Jahn–Teller distortion and electron redistribution afford Cu–Ni(OH)2 with abundant active adsorption sites, facilitating the complete hydrogen evolution kinetics. Abstract : Adsorption behavior determines catalytic efficiency in the hydrogen evolution reaction (HER). Thus, engineering catalytic adsorption sites provides an opportunity to investigate in depth the active areas of catalysts. Herein, we put forward an adsorption site engineering strategy to increase the density and intrinsic properties of adsorption sites in Ni(OH)2 by doping with Cu 2+ . Benefiting from the Jahn–Teller effect of Cu 2+, introducing lattice distortion affords Cu–Ni(OH)2 abundant active sites for intermediate conversion. Furthermore, combining experiments with DFT simulations, the doping of Cu 2+ in Ni(OH)2 causes local electron accumulation and modulated d electron state, affording Cu–Ni(OH)2 with preferable adsorption behavior for efficient intermediate conversion. As regards the electrochemical results, the obtained Cu–Ni(OH)2 integrated electrode exhibits appealing catalytic activity toward the HER at an overpotential of 53 mV to drive 10 mA cm −2 along with a low Tafel slope of 51 mV dec −1 . Hence, we believe that the adsorption site engineering strategy renders a valuable solution for designing efficient catalysts for use in alkaline HER.